Influence of epitaxial layer structure and cell structure on electrical performance of 6.5 kV SiC MOSFET. (1st August 2022) - Tian, Lixin; Du, Zechen; Liu, Rui; Niu, Xiping; Zhang, Wenting; An, Yunlai; Shen, Zhanwei; Yang, Fei; Wei, Xiaoguang
Abstract: Silicon carbide (SiC) material features a wide bandgap and high critical breakdown field intensity. It also plays an important role in the high efficiency and miniaturization of power electronic equipment. It is an ideal choice for new power electronic devices, especially in smart grids and high-speed trains. In the medium and high voltage fields, SiC devices with a blocking voltage of more than 6.5 kV will have a wide range of applications. In this paper, we study the influence of epitaxial material properties on the static characteristics of 6.5 kV SiC MOSFET. 6.5 kV SiC MOSFETs with different channel lengths and JFET region widths are manufactured on three wafers and analyzed. The FN tunneling of gate oxide, HTGB and HTRB tests are performed and provide data support for the industrialization process for medium/high voltage SiC MOSFETs.